Quantitative response of oil sunflower yield to evapotranspiration and soil salinity with saline water irrigation - Xin, He; Peiling, Yang; Shumei, Ren; Yunkai, Li; Guangyu, Jiang; Lianhao, Li (International Journal of Agricultural and Biological Engineering, 2016)
Appropriate application of water-salt-crop function model can optimize agricultural water management in regions with declining water supply, such as the Hetao district. Appropriate use of saline water is also based on the effects of irrigation water demand and water quality on crop growth quantitatively. Therefore, oil sunflower growth testing under both water and salt stress was completed from 2013 to 2014. Water salinity levels at 1.7 ds/m, 4 ds/m, 6 ds/m and 8 ds/m were used in the experiments. Two water deficit levels were reported, 60% and 80% of the irrigation quota, which were considered moderate and mild deficit levels, respectively. All treatments were applied in planting the oil sunflower in critical growing periods, namely, floral initiation, anthesis and maturity. Linear, Cobb-Douglas, quadratic and transcendental function models were used to simulate the relative yield, evapotranspiration (ET) and electrical conductivity (EC). The predictive ability and sensitivity of each model were then evaluated. Compared with salt stress, water stress exerted a more significant effect on the oil sunflower yield; the water parameters (a1 and a3) were most sensitive in the water-salt-crop function model. Oil sunflower was most sensitive to water and salt stress during anthesis. The transcendental function generally showed a relatively high sensitivity coefficient and a relatively small statistical error. Therefore, the transcendental function is the most appropriate model for simulating and predicting the yield of oil sunflower irrigated with saline water. Applying the water-salt-crop function model in planting of oil sunflower can help in the development and utilization of saline water in the Hetao district. Keywords: irrigation, water-salt production functions, saline water, water stress, salt stress, oil sunflower, evapotranspiration DOI: 10.3965/j.ijabe.20160902.1683 Citation: He X, Yang P L, Ren S M, Li Y K, Jiang G Y, Li L H. Quantitative response of oil sunflower yield to evapotranspiration and soil salinity with saline water irrigation. Int J Agric & Biol Eng, 2016; 9(2): 63－73.